Efficient mapping of an image processing application for a network-on-chip based implementation. (11th December 2009) - Da Silva, Marcus Vinicius Carvalho; Nedjah, Nadia; Mourelle, Luiza de Macedo
Network-on-chip (NoC) is considered the next generation of communication infrastructure, which will be omnipresent in different environments. In the platform-based methodology, an application is implemented by a set of collaborating intellectual properties (IPs) blocks. Increasing scale integration increases the number of possible IPs to be addressed on a NoC platform. In this paper, we propose a multi-objective evolutionary-based mapping of an image processing application on a NoC based platform. The IP mapping is driven by the area occupied, execution time and power consumption.